Biological Study of Protein Content in Various Types of Vegetables - Prazali , Arianteza; Azizah, Adilla Nur (Yayasan Siti Widhatul Faeha, 2025)
Vegetables, as a source of plant-based protein, play a significant role in a healthy and sustainable diet. Several vegetables from the Fabaceae, Brassicaceae, and Amaranthaceae families are known to contain high levels of protein, making them viable alternatives to animal-based protein. This study aims to examine the potential of vegetables as alternative protein sources in supporting food security and sustainability. A literature review was conducted to analyze the protein content in various vegetables based on scientific literature from indexed journals and trusted organizations. The analysis was performed descriptively, comparing the protein content of vegetables based on their type, growth phase, and growing environment, while also identifying the biological roles of protein in plants. The results indicate that protein is a food substance made up of amino acids, which functions to build and regulate the body. Of the 20 amino acids, 8 are essential for adults and 10 for growing children. High-protein vegetables include spinach (Amaranthus sp.) with 3.5 g of protein per 100 g, broccoli (Brassica oleracea) 2.8 g, soybeans (Glycine max) 18.2 g, peanuts (Arachis hypogaea) 21 g, potatoes (Solanum tuberosum) 2%, and edamame (Glycine max) 18.5 g per 155 g. These vegetables are rich in protein, vitamins, and minerals essential for the body and offer health benefits such as improved stamina, support for bone health, and reduced risk of certain diseases. The study concludes that vegetables and legumes with high protein content can serve as an optimal alternative source of nutrition to support a healthy diet.